ANALISIS KINERJA IMPLEMENTASI ALGORITMA DIJKSTRA UNTUK MENCARI RUTE TERDEKAT DARI BALEEDAH KE PERPUSTAKAAN KAWALUYAAN DENGAN MENGGUNAKAN PYTHON - COMPUTING INFORMATIKA; Yaya Suharya; Sukiman; Jahwan (Program Studi Teknik Informatika FTI UNIBBA, 2022)
ABSTRACT: With the library opened by the government, thus many students or students come to look for books to be a reference for various tasks, for example researchers themselves who often go to the Kawaluyaan Library Bandung to find thesis reviews and the distance that researchers travel from the research house to the Kawaluyaan Library quite far, from the experience of researchers so far who have been to the Bandung Kawaluyaan Library quite often and also to minimize the use of motorbike gasoline, the author is looking for the nearest or shortest route to go to the Bandung Kawaluyaan Library. To solve this research problem, researchers use the Dijkstra Algorithm where this algorithm can solve short path problems experienced by researchers, and data collection methods carried out by researchers, namely observation, literature study, problem identification, analysis, design, implementation and results